Dental Anxiety in Northern Norway. Epidemiologic Assessment of Dental Anxiety in the Troms County - the TOHNN-study - Valcacio Guedes Neto, Manoel (UiT Norges arktiske universitet, 2017)
Objectives. The aim of this study was to describe the prevalence of dental anxiety (DA) in the Troms county and to investigate the association of DA and variables of socio-economic status, geographic distribution, gender, dental care habits, and oral health status. Methods. Data from the Tromstannen – Oral health in Northern Norway (TOHNN) study was used. Dental anxiety was assessed with the aid of the Corah’s Dental Anxiety Scale (DAS) in a randomly selected sample representative of the population in the Troms county, northern Norway (n=1936). Participants answered a comprehensive questionnaire and went through a clinical examination where decayed teeth (DT) and decayed surfaces (DS) were assessed. The findings were statistically analyzed using the software SPSS, where the person’s chi-square test was used for the bivariate analysis and logistic regression analysis was used to examine predictors to DA. Results. The prevalence of severe dental anxiety among the participant was 9,5% and more women than men were affected (OR=3,053). There was a significance difference in means of DT and DS between DA groups (t-test, p<0,001). Conclusion. High and severe DA is more prevalent among women, individuals with lower education and lower income and it presents a negative influence in oral health status.